An investigation of the attitudes, perceptions, knowledge, and understandings of school counselors in Saudi Arabia. - Alotaibi, Turki (2018)
INTRODUCTION: The Saudi Arabian Ministry of Education established the 'General Directorate of Guidance and Counseling' in the Kingdom of Saudi Arabia (Saudi Arabia) in 1981. In 2003 approximately 4,000 school-based counsellors were working in schools in Saudi Arabia. Student counselling programmes in Saudi schools cover the areas of preventative, educational, vocational, and religious and moral counselling. Although school-based counselling is well established in Saudi Arabia there are very few studies researching school-based counselling in Saudi schools that have been identified in the literature. There is evidence to show that school-based counsellors face numerous problems in practice.